Knowledge, Attitudes, and Practices of Women Engaged in Sex Work: An Evaluation of Source of Interventions - Salve, Mark Anthony (Silliman Journal, 2024)
This study sampled 30 FSWs who have been involved with the intervention activities of the Silliman University Extension Office. Data were collected through personal interviews with the women using a questionnaire guide. With regards to the KAP variables and source of intervention, the results revealed no significant relationship between the source of intervention and knowledge (p = .41). Similarly, no significant relationship was established between the source of intervention and attitude (p = .91), as well as between the source of intervention and practice (p = .76). Meanwhile, the research outcome between the KAP variables showed significant relationships, as follows: knowledge and attitude (p < .001), attitude and practice (p = .01), and knowledge and practice (p < .001). For the relationship between demographic variables and practice, a significant difference was exhibited between the age categories of the sex workers (U = 32.0, p = .04) and years of engagement (U = 53.0, p = .02). In contrast, no significant difference was manifested between marital status (U = 99.5, p =.84) and educational attainment (U = 103.0, p = .84) categories. The results of this study can guide the formulation of efficient strategies for improving the health and well-being of FSWs.